Perlindungan Hukum terhadap Konsumen yang Dirugikan dalam Belanja Online di Marketplace - Wisman, Felina Laurensia (Journal Evidence Of Law, 2024)
This study aims to evaluate the legal protection available to consumers who suffer losses while shopping online and to examine the legal framework regulating the marketplace in Indonesia. The research employs both legislative and conceptual approaches, as well as literature review and analysis of legal documents. Findings indicate that although laws such as Law Number 8 of 1999 on Consumer Protection and Law Number 11 of 2008 on Electronic Information and Transactions (ITE) are in place, their implementation faces challenges, particularly in enforcing consumer rights and addressing online fraud. Existing Government Regulations and Ministerial Regulations are in effect but have not fully resolved issues related to seller liability, dispute resolution, and transaction security. The distinction between physical and digital products under different legal frameworks adds complexity to consumer protection. Lack of consumer awareness and unclear legal provisions exacerbate the problem. Key recommendations include improving consumer information, strengthening regulations and legal actions against violations, and updating laws to keep pace with technological advances and digital market dynamics.